Combined effects of green manure and zinc oxide nanoparticles on cadmium uptake by wheat (Triticum aestivum L.). (July 2022) - Chen, Fu; Bashir, Arooj; Zia ur Rehman, Muhammad; Adrees, Muhammad; Qayyum, Muhammad Farooq; Ma, Jing; Rizwan, Muhammad; Ali, Shafaqat
Abstract: Cadmium (Cd) toxicity in agricultural soils is serious concern these days which needs continuous attention. Little is known about the combined use of berseem and/or maize residues soil applied as a green manure alone or along with foliar dressing of zinc oxide nanoparticles (ZnONPs) on Cd accumulation in wheat ( Triticum aestivum L.). A pot experiment under ambient conditions with wheat grown in Cd-contaminated soil was performed after soil applied different green manure amendments and foliar dressing of ZnONPs was done during plant growth and plants were harvested at full maturity. Compared with control, plant growth attributes and biomass of above ground parts substantially increased with applied amendments being maximum with combined use of ZnONPs + B75 (berseem residue, 75 mg/kg) followed by ZnONPs + M75 (maize residue, 75 mg/kg). All the treatments improved the leaf chlorophyll contents and improved the leaf antioxidant enzyme activities thereby reduced the leaf electrolyte leakage. The Cd accumulation in roots and aboveground parts of the wheat was reduced especially in ZnONPs + B75 followed by ZnONPs + M75. The higher rate of soil applied amendments along with NPs minimized the available Cd in soil extracts but soil post-harvest pH was not much affected by the applied amendments. In conclusion, incorporation of berseem and maize residues as a green manure applied in Cd-contaminated soil combined with foliar NPs may decrease Cd phytoavailability and its accumulation in wheat grains. However, substantial field studies are required under various environmental conditions before final recommendations at field levels. Graphical abstract: Image 1 Highlights: The highest Cd concentrations were found in plants without any treatments. ZnONPs and green manure increased growth and biomass of wheat. ZnONPs and green manure enhanced activities of antioxidants enzymes in leaves. ZnONPs and green manure decreased Cd contents in grains of wheat.